Synergies of co-infecting pathogens, sea lice (Lepeophetheirus salmonis) and Moritella viscosa, are impacted by exposure order, and host response to initial infection - Wenlong Cai; Liang Zhong; Kathleen Parrish; Surendra Kumar; Khalil Eslamloo; Eyesun Fajei; Shona K. Whyte; Sara L. Purcell; Ladan Jahangiri; Runsheng Li; Albert Caballero Solares; Richard G. Taylor; et al. (Aquaculture, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

High Degree of Genetic Heterogeneity for Hereditary Cerebellar Ataxias in Australia - Ce Kang; Christina Liang; Kate E. Ahmad; Yufan Gu; Sue-Faye Siow; James G. Colebatch; Scott Whyte; Karl Ng; Philip D. Cremer; Alastair J. Corbett; Ryan L. Davis; Tony Roscioli; et al. (The Cerebellum, 2019)

Mechanisms of subzero growth in the cryophile Planococcus halocryophilus determined through proteomic analysis - Isabelle Raymond‐Bouchard; Karuna Chourey; Ianina Altshuler; Ramsunder Iyer; Robert L. Hettich; Lyle G. Whyte (Environmental Microbiology, 2017)
Summary The eurypsychrophilic bacterium Planococcus halocryophilus is capable of growth down to −15°C, making it ideal for studying adaptations to subzero growth. To increase our understanding of the mechanisms and pathways important for subzero growth, we performed proteomics on P . halocryophilus grown at 23°C, 23°C with 12% w/v NaCl and −10°C with 12% w/v NaCl. Many proteins with increased abundances at −10°C versus 23°C also increased at 23C‐salt versus 23°C, indicating a closely tied relationship between salt and cold stress adaptation. Processes which displayed the largest changes in protein abundance were peptidoglycan and fatty acid (FA) synthesis, translation processes, methylglyoxal metabolism, DNA repair and recombination, and protein and nucleotide turnover. We identified intriguing targets for further research at −10°C, including PlsX and KASII (FA metabolism), DD‐transpeptidase and MurB (peptidoglycan synthesis), glyoxalase family proteins (reactive electrophile response) and ribosome modifying enzymes (translation turnover). PemK/MazF may have a crucial role in translational reprogramming under cold conditions. At −10°C P . halocryophilus induces stress responses, uses resources efficiently, and carefully controls its growth and metabolism to maximize subzero survival. The present study identifies several mechanisms involved in subzero growth and enhances our understanding of cold adaptation.

Microscopic characterization of the bacterial cell envelope of Planococcus halocryophilus Or1 during subzero growth at −15 °C - N. C. S. Mykytczuk; J. R. Lawrence; C. R. Omelon; G. Southam; L. G. Whyte (Polar Biology, 2016)

Novel sulfur‐oxidizing streamers thriving in perennial cold saline springs of the Canadian high Arctic - Thomas D. Niederberger; Nancy N. Perreault; John R. Lawrence; Jay L. Nadeau; Randall E. Mielke; Charles W. Greer; Dale T. Andersen; Lyle G. Whyte (Environmental Microbiology, 2009)
Summary The perennial springs at Gypsum Hill (GH) and Colour Peak (CP), situated at nearly 80°N on Axel Heiberg Island in the Canadian high Arctic, are one of the few known examples of cold springs in thick permafrost on Earth. The springs emanate from deep saline aquifers and discharge cold anoxic brines rich in both sulfide and sulfate. Grey‐coloured microbial streamers form during the winter months in snow‐covered regions of the GH spring run‐off channels (−1.3°C to 6.9°C, ∼7.5% NaCl, 0–20 p.p.m. dissolved sulfide, 1 p.p.m. dissolved oxygen) but disappear during the Arctic summer. Culture‐ and molecular‐based analyses of the 16S rRNA gene (FISH, DGGE and clone libraries) indicated that the streamers were uniquely dominated by chemolithoautotrophic sulfur‐oxidizing Thiomicrospira species . The streamers oxidized both sulfide and thiosulfate and fixed CO 2 under in situ conditions and a Thiomicrospira strain isolated from the streamers also actively oxidized sulfide and thiosulfate and fixed CO 2 under cold, saline conditions. Overall, the snow‐covered spring channels appear to represent a unique polar saline microhabitat that protects and allows Thiomicrospira streamers to form and flourish via chemolithoautrophic, phototrophic‐independent metabolism in a high Arctic winter environment characterized by air temperatures commonly below −40°C and with an annual average air temperature of −15°C. These results broaden our knowledge of the physical and chemical boundaries that define life on Earth and have astrobiological implications for the possibility of life existing under similar Martian conditions.

Angiogenesis in rat aortic rings stimulated by very low concentrations of serum and plasma - Ronald S. Go; Erik L. Ritman; Whyte G. Owen (Angiogenesis, 2003)

Effect of Maintaining Rainbow Trout in Creosote Microcosms on Lens Optical Properties and Liver 7-Ethoxyresorufin- O -Deethylase (EROD) Activity - J. J. Whyte; K. L. Herbert; N. A. Karrow; D. G. Dixon; J. G. Sivak; N. C. Bols (Archives of Environmental Contamination and Toxicology, 2000)